Windows 10 for the Internet of Things controlling internet-connected devices from Raspberry Pi - Bell, Charles (Apress, 2021)
Manage and control Internet-connected devices from Windows and Raspberry Pi. Master the Windows 10 IoT Core application programming interface and feature set to develop Internet of Things applications on the Raspberry Pi using your Windows and .NET programming skills. New in this edition is coverage of enterprise-level tools and features in the Windows 10 IoT Enterprise server operating system, allowing you to manage IoT solutions having large numbers of devices and to deploy applications to enterprise-grade hardware. Windows 10 for the Internet of Things presents a set of example projects covering a wide range of techniques designed specifically to jump start your own Internet of Things creativity. You'll learn everything you need to know about Windows IoT Core to develop Windows and IoT applications that run on single board computers such as the Raspberry Pi. You'll learn to develop for the Raspberry PI using native Windows and all the related programming skills that you have built up from developing desktop and mobile applications. This book provides just the help you need to get started in putting your Windows skills to use in a burgeoning new world of development for small devices that are ubiquitously connected to the Internet. You will: Know Windows 10 on the Raspberry Pi Read sensor data and control actuators Connect to and transmit data into the cloud Remotely control your devices from any Windows device Develop IOT applications under Windows using C#, C++, and Visual Basic Store your IOT data in a database for later analysis.